Thermal Stability of Iron Micro- and Nanopowders after Electron Beam Irradiation; Key Engineering Materials; Vol. 712 : Advanced Materials for Technical and Medical Purpose (AMTMP 2016) - Mostovshchikov A. V. Andrey Vladimirovich; Ilyin A. P. Aleksandr Petrovich; Egorov I. S. Ivan Sergeevich; Ismailov D. V. Daniar (Electrophysical and Electrochemical Methods and Technologies of Materials Treatment, 2016)
Title screen